Identificación de los géneros de ácaros causantes de sarna en caninos con dermatitis presentes en el Recinto el Deseo del Cantón Milagro - Villamar Reyes, John Steve (2024)
The present work seeks to observe the prevalence of the different types of mites that cause scabies in canines with dermatitis from the Recinto del Deseo in the Milagro Canton. How do we know that scabies is a disease that mainly affects the skin in which it causes dermal problems such as shedding extreme itchy hair among other diseases. In dogs, it will mainly cause intense itching and alopecia, the most common being the so-called scabies, which primarily affects those who have direct contact with the infected. 50 samples were evaluated and the deep scraping method was used to identify the presence and different genera of mites that cause scabies in canines with dermatitis present in the Deseo Campus of Cantón Milagro where there was a prevalence of 18%. The genus of mite with the highest prevalence is Sarcoptes scabiei 56%, followed by Demodex canis 33%, and in smaller numbers is Otodectes cynotis 11%. The identification of scabies according to sex is 52% in males and 48% in females. According to age, there was a higher prevalence of scabies in canines from 1 to 4 years of age of 46% and a lower prevalence in those from 9 to 13 years of age with 8%. The identification of mange according to the breed, it was determined that canines that are mixed breeds are the most affected with 54% while a lower prevalence was observed in Pitbull breeds 12%, Labrador 8%, Golden 6% Siberian Husky 2%.